PATH-28. RE-DEFINING CLONALITY OF THE TERT PROMOTER MUTATION WITH DEEP SEQUENCING AND MAXIMAL SAMPLING OF NEWLY DIAGNOSED AND RECURRENT GBM AND OLIGODENDROGLIOMA. (12th November 2021) - Appin, Christina; Suwala, Abigail K; Hilz, Stephanie; Mathur, Radhika; Smirnov, Ivan; Hong, Chibo; Stevers, Nicholas; Shai, Anny; Berger, Mitchel; Chang, Susan; Phillips, Joanna; Costello, Joseph
Abstract: TERT promoter mutation (TPM), found in over 80% of IDH -wildtype glioblastomas (GBMs) and oligodendrogliomas, leads to reactivation of telomerase and consequently tumor cell immortalization, which is potentially reversible. TERT could therefore serve as an effective target in treating tumors with TPM, if TPM is present throughout the tumor. Previous studies using a single sample or minimal sampling per tumor have shown potentially conflicting results, suggesting TPM is clonal in some cases and subclonal in others. Here we use spatially mapped tumor samples representing maximal tumor sampling to address this critical issue. Sanger sequencing was performed on 311 newly diagnosed and recurrent tumor samples from 19 IDH -wildtype GBMs and 10 oligodendrogliomas. To validate Sanger sequencing and resolve potentially ambiguous samples, deep amplicon sequencing was performed on 164 samples. To determine tumor purity and TERT expression levels, whole exome sequencing (164 samples) and RNA-Seq (129 samples) data sets were analyzed computationally. Sanger and amplicon sequencing showed that TPM was present in 305 of 311 samples (98.1%). TPM was not detected in 6 samples which had tumor purity estimates too low to be accurately determined by FACETS and lacked evidence of any driver mutation. Variant allele frequencies (VAFs) of TPM showed high positive correlation with those of clonal alterations in GBMs ( r (90) = .93, p < .0001) and oligodendrogliomas ( r (48) = .96, p < .0001). TPM VAFs also showed high positive correlation with tumor purity in both GBMs ( r (112) = .92, p < .0001) and oligodendrogliomas ( r (48) = .89, p < .0001). TPM VAF showed a moderate positive correlation with TERT expression in GBMs ( r (78) = .40, p < .001) and oligodendrogliomas ( r (47) = .49, p < .001). Therefore, TPM is a tumor-wide, clonal mutation in both newly diagnosed and recurrent GBMs and oligodendrogliomas. TPM VAF is moderately correlated with TERT expression.